Motivation for Polygamous Marriage in Islamic Boarding School Community (Case Study in Maccopa Maros Community) - St.Wijdanah Ram, Tahir Kasnawi, Suparman Abdullah, Sakaria Anwar (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This article aims to analyze the motives behind polygamous marriages in the Maccopa Maros Islamic boarding school community. The method used in this research is a case study qualitative method using in-depth interviews, observation, and document studies in collecting data. Informants The informants of this research were categorized into three groups, the first was a key informant, namely one of the managers (Secretary General) of the Darul Istiqamah Islamic Boarding School who was considered to understand the ins and outs of the Maccopa community, the second was an ordinary informant with 4 pairs of polygamous couples who will be the research subject, which is selected purposively. They are a harmonious polygamous couple in the Maccopa Maros Islamic Boarding School community with criteria 1. A polygamous marriage known to the first wife. 2. Polygamous couples whose second marriage age is 10 years and above, because it is considered that at 10 years of age polygamous marriage has passed the adaptation period and has passed critical periods of marriage. The third is expert informants who have expertise in the fields of religion and society. The number of expert informants is 1 person. The results of the study of polygamous marriages in terms of rational choice theory found the fact that they have motivation for selfinterest that contains values or choices. There are several reasons they carry out polygamous marriages, including as an application to Islamic da'wah, increasing leadership in building households, setting a good example of polygamy to the community, and to save themselves from sin.